Analisis Implementasi Sistem Penilaian Perilaku Kerja Pegawai pada Badan Kepegawaian Daerah Provinsi Jawa Barat - Azzahra, Alya; Supriatna, Metha Djuwita (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2023)
Behavioral appraisal for civil servants is part of performance appraisal by using a 360-degree method. This method involves a team which consists of ratee’s direct superiors, co-workers, ratee, and subordinates, to evaluate civil servant’s work behavior in accordance with the provisions of the legislation. However, in practice there are some obstacles, such as in the Regional Personnel Agency (BKD: Badan Kepegawaian Daerah of West Java Province. Therefore, this study aimed to: 1) find out the behavior appraisal system with the 360 method at the West Java BKD, 2) improve the behavior appraisal system, and 3) find out the results of the evaluation of the behavior appraisal system improvement. A qualitative method with a descriptive approach was used in this study, through interviews and observations. As result, there were three problems i.e. the behavioral appraisal instrument used by the BKD did not fully support performance appraisal, the performance appraisal rater were incompetent, and the results of the behavior appraisal were only in the form of values that would be used as the basis for providing additional employee allowance (or TPP: Tambahan Penghasilan Pegawai). Therefore, improvements were made to the system by designing comprehensive behavioral assessment guidelines and then evaluating the improvements to the system. So that the compiled guidelines can be used as a reference for the implementation of civil servants’ behavior appraisal at the BKD West Java Province.